Correlations between speciation of Zn in sediment and Zn concentrations in different soft tissues of the gastropod Mollusc Telescopium telescopium collected from intertidal areas of Peninsular Malaysia - Arifin, Noorhaidah; Yap, Chee Kong (Universiti Putra Malaysia, 2010)
The aim of this study was to relate the Zn level in the different tissues of Telescopium telescopium to the Zn levels of surface sediment of the gastropod habitat. Zn concentrations were determined in the different soft tissues (foot, cephalic tentacle, mantle, muscle, gill, digestive caecum and remaining soft tissues) of T. telescopium and in the sediments collected from 17 intertidal areas of Peninsular Malaysia, where the snails were collected. Total Zn concentrations and speciation of Zn of the surface sediment were correlated with the Zn concentrations measured in the different soft tissues of T. telescopium. The results showed that significant (p <0.01) correlations were observed between Zn concentrations in mantle, muscle, gill, and remaining soft tissues with non-resistant Zn in sediment; Zn concentration in gill with resistant Zn in sediment; mantle, muscle, gill, and remaining soft tissues with acid reducible Zn in sediment; gill and remaining soft tissues with oxidisable-organic Zn in sediment. The pattern of Zn distribution showed that digestive caecum of T. telescopium in all 17 sites always contained the highest coiicentration of Zn, except for Kuala Sg. Ayam. Therefore, the present results generally supported the use of different soft tissues of T. telescopium as a more accurate biomonitoring organ for Zn, besides the total soft tissues.